Distributed Electric Propulsion on a Joined-Wing Air-Taxi - Brand, Darren Mark (University of the Witwatersrand, Johannesburg, 2024)
Urban Air Mobility (UAM) is a form of aerial transportation within urban areas with the main intention of easing traffic congestion. Electric Vertical Take-off and Landing (EVTOL) air-taxis are currently in development, but no single configuration has been identified as superior for UAM. There is still scope for alternate designs to be explored. A major obstacle to successful UAM operations is the combination of high energy requirements for VTOL and low battery energy densities, thereby affecting operational aircraft range. Aerodynamic efficiency has been identified as a critical factor for achieving maximum flight range while electric battery technology is matured. It is proposed that an air-taxi which combines Distributed Electric Propulsion (DEP) with a joined-wing may achieve superior aerodynamic efficiency compared to other air-taxi designs. A joined-wing air-taxi capable of carrying four passengers and a pilot has been developed with four alternative DEP configurations. These aircraft are herein investigated and compared against one another. A computational approach was followed using STAR- CCM+ to evaluate the flow characteristics and forces around the aircraft for both climb and cruise conditions. It was found that a “Non-DEP” configuration with four proprotors can achieve up to 5% higher aerodynamic efficiency than a DEP variant. However, this configuration suffers with poor lifting capability at high angles of attack. The sensitivity of aerodynamic efficiency to changes in the number of proprotors and their spacing was seen to be negligible according to this investigation.
A research report submitted in fulfillment of the requirements for the Master of Science in Aeronautical Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Air-Taxi; UAM; DEP; VTOL; Joined-Wing; SDG-7: Affordable and clean energy; SDG-13: Climate action